2019
DOI: 10.1002/adfm.201900259
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Surmounting Blood–Brain Tumor Barrier Through Both Transcellular and Paracellular Pathways to Target Brain Metastases

Abstract: Brain metastases are one of the most difficult malignancies to treat owing to their location and mostly multifocal and infiltrative growth. Chemotherapy, which is often effective against tumors outside the brain, offers some hope for brain metastases. However, the efficacy of systemic drug delivery to brain metastases is extremely limited due largely to the blood–brain tumor barrier (BTB). Herein, it is reported that minoxidil‐loaded hyaluronic acid–tethered nanoparticles (M@H‐NPs) can efficiently and speciall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…Some literatures reported that although the tight junctions of BBB are slightly disrupted in the early stage of glioma, most nanomaterials cannot traverse the BBB to accumulate in glioma for early diagnosis and therapy. [ 8,21,22 ] In order to explore whether the metastatic cancer cell membrane‐coated nanoparticles can cross the BBB to image glioma tumor cells in the early stage, an orthotopic mouse model bearing luciferase‐expressing human glioblastoma tumor (U87MG‐Luc) was used to perform the analysis. The glioma cell activity was measured by bioluminescence imaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literatures reported that although the tight junctions of BBB are slightly disrupted in the early stage of glioma, most nanomaterials cannot traverse the BBB to accumulate in glioma for early diagnosis and therapy. [ 8,21,22 ] In order to explore whether the metastatic cancer cell membrane‐coated nanoparticles can cross the BBB to image glioma tumor cells in the early stage, an orthotopic mouse model bearing luciferase‐expressing human glioblastoma tumor (U87MG‐Luc) was used to perform the analysis. The glioma cell activity was measured by bioluminescence imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Brain metastasis is a common complication of most tumors, including lung cancer, breast cancer, and melanoma. [ 22 ] About 20–30% of these malignant tumors can metastasize into the brain to form secondary brain tumors. [ 23 ] Obviously, these tumor cells are able to cross the blood–brain barrier into the brain.…”
Section: Introductionmentioning
confidence: 99%
“…The large cavities of mesopores in AuNFs enabled encapsulation of small‐molecule cargos such as chemotherapeutics for local delivery. Doxorubicin (DOX), an ideal model drug for its broad anticancer activity and relatively stable fluorescence for in vitro and in vivo tracking, was chosen to evaluate the drug‐loading efficiency of AuNFs. Through thiol (SH) groups, a Raman reporter, 4‐aminothiophenol (4‐ATP), was linked onto the surface of AuNFs.…”
Section: Introductionmentioning
confidence: 99%
“…Through thiol (SH) groups, a Raman reporter, 4‐aminothiophenol (4‐ATP), was linked onto the surface of AuNFs. Hyaluronic acid (HA), a natural polysaccharide with high affinity for CD44, was further grafted onto the surface of AuNFs to obtain an HA‐4‐ATP‐AuNFs‐DOX nanosystem via the formation of amide bonds between carboxylic groups of HA and amino groups of 4‐ATP. In this nanosystem, the grafted HA not only acted as the cap for trapped DOX within mesopores but also endowed AuNFs with stability, biocompatibility, CD44‐overexpressing tumor target ability, and functional groups for Raman reporter‐linking.…”
Section: Introductionmentioning
confidence: 99%
“…These biomimetic nanocomposites can facilitate the mimicking of the tumor microenvironment that results in a wide range of favorable applications, such as specific targeting and prolonged circulation time. Although utilizing This strategy can treat cancer tumor models by using some cell membrane-coated nanostructures, [ 76 , 77 ] but, to use this strategy to treat brain tumors is rarely explored [ 78 ]. Over the years, there are numerous NPs that were successfully applied for brain tumors, which are summarized in Table 3 .…”
Section: Bbb Penetrating Nanoplatforms (Nfs) In Biomedical Applicamentioning
confidence: 99%